Performance and emission evaluation of a CI engine fueled with preheated raw rapeseed oil (RRO)-diesel blends - Hazar, Hanbey; Aydin, Hueseyin (Elsevier Sci Ltd, 2010)
Many studies are still being carried out to find out surplus information about how vegetable based oils can efficiently be used in compression ignition engines. Raw rapeseed oil (RRO) was used as blended with diesel fuel (DF) by 50% oil-50% diesel fuel in volume (050) also as blended with diesel fuel by 20% oil-80% diesel fuel in volume (020). The test fuels were used in a single cylinder. four stroke, naturally aspirated, direct injection compression ignition engine. The effects of fuel preheating to 100 degrees C on the engine performance and emission characteristics of a CI engine fueled with rapeseed oil diesel blends were clarified. Results showed that preheating of RRO was lowered RRO's viscosity and provided smooth fuel flow Heating is necessary for smooth flow and to avoid fuel filter clogging. It can be achieved by heating RRO to 100 degrees C. It can also be concluded that preheating of the fuel have some positive effects on engine performance and emissions when operating with vegetable oil. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Diesel engine; Preheating; Rapeseed oil; Engine performance; Emissions